2016
DOI: 10.9774/gleaf.4700.2016.se.00005
|View full text |Cite
|
Sign up to set email alerts
|

The Ethical Responsibility of Companies Towards Animals: A Study of the Expressed Commitment of the Fortune Global 200

Abstract: Reasonable arguments can be advanced to show that companies have an ethical responsibility towards animals. However, hardly any empirical research has been conducted to establish whether companies acknowledge these responsibilities and how they articulate them. This study shows that 47% of the 200 largest companies in the world make statements of ethical responsibility towards animals. The findings show great divergence in the expressed commitment towards animal welfare among these companies. Companies that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 72 publications
2
10
0
Order By: Relevance
“…The overall findings are similar to findings presented by Janssens and Kaptein, who analysed the websites of the 200 largest corporations in the world (selected from the 2012 Fortune Global 500 list) for statements of responsibility towards animals [19]. Their assessment of 21 companies involved in animal-based food products concluded that 76% of these companies had made statements of responsibility towards animals, a broadly similar figure to the 71% (2012) and 70% (2013) of the companies covered by the Benchmark who acknowledged farm animal welfare as a business issue.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The overall findings are similar to findings presented by Janssens and Kaptein, who analysed the websites of the 200 largest corporations in the world (selected from the 2012 Fortune Global 500 list) for statements of responsibility towards animals [19]. Their assessment of 21 companies involved in animal-based food products concluded that 76% of these companies had made statements of responsibility towards animals, a broadly similar figure to the 71% (2012) and 70% (2013) of the companies covered by the Benchmark who acknowledged farm animal welfare as a business issue.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, companies regularly put their actions or results in documents of marginal importance or ‘hidden’ documents of a low status or with a temporary nature (e.g., company magazines or blogs) rather than in online corporate-level documents. This limits communication about such actions or outcomes [19]. There may be various reasons for this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past few decades, new, more demanding ethical norms for organizations have emerged concerning bribery (Weber and Getz 2004), insider trading (Moore 1990), salaries (Nichols and Subramaniam 2001), fair trade (Jaffee 2010), the natural environment (Gladwin et al 1995), animals (Janssens and Kaptein 2014), lobbying (Hamilton and Hoch 1997), supply chain responsibility (Van Tulder et al 2009), human rights (Muchlinski 2012), and investing (Hudson 2005). These ethical norms are developed in response to new issues (such as bitcoins), trends (such as globalization), scandals and crisis (such as the financial-economic crisis at the end of the first decade of this century), information (such as about the damage of corruption), paradigms (such as stakeholder instead of shareholder thinking, Paine 2002), and new theories (such as an ethics of care, Lawrence and Maitlis 2012).…”
Section: Introductionmentioning
confidence: 99%